PERBANDINGAN KINERJA ANALITIK HASIL PENENTUAN ION LOGAM Pb DENGAN MENGGUNAKAN SPEKTROFOTOMETER SERAPAN ATOM DI BERBAGAI LABORATORIUM SAMARINDA - arifin syam syam; bohari Yusuf; Aman Sentosa Panggabean (JURNAL ATOMIK, 2021)
The study about the comparison of analytical performance of the determination of Pb metal ions using Atomic Absorption Spectrophotometer in various laboratories in samarinda has been conducted. The validated methods are linearity, detection limits, quantity and precision limits. The results showed, a standardized regression test obtained by laboratory A, a value of R2 ≥ 0.4103, laboratory B a value of R2 ≥ 0.983 and laboratory C, a value of R2 ≥ 0.000. The detection limit found at laboratory A was 0.6728 µg/L, laboratory B was 0.1989 µg/L and laboratory C was 0.0001 µg/L. The quantization limit obtained by laboratory A was 0.6817 µg/L, laboratory B was 0.6063 µg/L and laboratory C was 0.0001 µg/L. The precision test of laboratory A was 7.2208, laboratory B was 5.4557 and laboratory C was 0,000. The result of determining Pb of gas station soil samples in laboratory A is 0.737 µg/L and laboratory B is 0.391 µg/L, so that means they have exceeded the quality standards set by the Indonesian National Standard (INS).